EKSISTENSI DAN NILAI-NILAI KEARIFAN KOMUNITAS SAMIN DI KUDUS DAN PATI - Alamsyah, Alamsyah (HUMANIKA, 2015)
Samin community in Sukolilo Pati and Undaan Kudus is a potrait of cultural diversity of our nation. Samin Community that still survive today, in the historical context of existence, has existed since the late 19th century. This community has a contribution in realizing Indonesian Independence by fighting against Dutch colonialist. Public ignorance towards history, culture and Saminâ€™s thought makes people perceive that this comunity â€œDo as they own wishesâ€ without heeding the public regulations and norms. Negative stereotypes appears about this community which leads to oddity, peculiarity or anything unnatural (nyleneh). Whereas this community has cultural values based on the local wisdom (local wisdom). Samin wisdom can be an example in building diversity, integration and social harmony.